Characterization of DOM and Its Interactions with Invasive Quagga Mussels in Lake Michigan - (:unkn) unknown (My University, 2016)
Green Bay is the largest freshwater estuary in the Laurentian Great Lakes and receives disproportional terrestrial inputs. While seasonal hypoxia and the formation of “dead zones” in Green Bay have received increasing attention, there are no systematic studies on the dynamics of dissolved organic matter (DOM) and its linkage to the development of hypoxia. During summer 2014, bulk dissolved organic carbon (DOC) analysis, UV-vis spectroscopy, and fluorescence excitation-emission matrices (EEMs) coupled with PARAFAC analysis were used to quantify the abundance, composition and source of DOM and their spatiotemporal variations in Green Bay, Lake Michigan. Concentrations of DOC ranged from 202 to 571 µM-C (average = 361±73 µM-C) in June and from 279 to 610 µM-C (average = 349±64 µM-C) in August. In both months, absorption coefficient at 254 nm (a254) was strongly correlated to bulk DOC and was most abundant in the Fox River, attesting to a dominant terrestrial input. Non-chromophoric DOC comprised, on average, ~32% of the bulk DOC in June with higher terrestrial DOM and ~47% in August with higher aquagenic DOM, indicating that autochthonous and more degraded DOM is of lower optical activity. PARAFAC modeling on EEM data resulted in four major fluorescent DOM components, including two terrestrial humic-like, one aquagenic humic-like, and one protein-like component. Variations in the abundance of DOM components further supported changes in DOM sources. Mixing behavior of DOM components also indicated that while bulk DOM behaved quasi-conservatively, significant compositional changes occurred during transport from the Fox River to the open bay. Quagga mussel infestation is another issue in the Great Lakes that has caused significant changes in food web structure and ecological function over the past decade. Nevertheless, linkages between invasive species and dynamics of carbon and nutrients in Lake Michigan are less clear. We report here yields of dissolved organic matter (DOM) and nutrients from quagga mussels as well as chemical composition and size spectra of excreted DOM. Clearance rates of different sized microparticles indicate that quagga mussel ctenidial fibers can efficiently retain DOM as small as 0.5 µm. Smaller mussels have higher DOM excretion rates (0.076±0.004 µmol-C mgDW-1 d-1) compared to larger mussels (0.012±0.0002 µmol-C mgDW-1 d-1). Nitrogen excretion rate was up to 0.24±0.01 µmol-N mgDW-1 d-1, 3 times higher than dissolved organic carbon (DOC), while inorganic phosphorus excretion was only 0.0076±0.0030 µmol-P mgDW-1 d-1. Excreted DOM was mostly chromophoric and high-molecular-weight in nature with a colloidal size spectrum centered at 1-5 kDa, had a low C/N but higher N/P ratio, and was comprised of up to 78% carbohydrates with high abundance of structural polysaccharides. Fluorescence EEMs and PARAFAC analysis identified two major fluorescent DOM components: a tryptophan-like and a UVC humic-like, suggesting that excreted DOM could be potentially labile. Compared with field measurements, only ~12% of organic matter consumed by quagga mussels is excreted/egested, and the vast majority is likely respired as CO2, potentially contributing to its supersaturation in the water column and changes in carbon dynamics in Lake Michigan after the colonization of invasive quagga mussel.
Keywords: CDOM; Dissolved Organic Matter; Excretion; Green Bay; Lake Michigan; Quagga Mussels